Introduction to Geographic Information Systems - John Lagrosa; Chris Demers; Michael Andreu (EDIS, 2012)
A GIS can be used in land management to document existing conditions, plan future operations, and archive completed work. Farming applications include soil productivity for different crops, crop yield prediction, and determining fertilizer and pesticide application rates. Forestry applications include estimating forest stand acreage, determining forest stand characteristics, and determining where to harvest. This 4-page fact sheet was written by John Lagrosa, Chris Demers, and Michael Andreu, and published by the UF Department of School of Forest Resources and Conservation, March 2012.